The Effectiveness of Simultaneous Roundtable in Teaching Writing At EFL Setting - Mohammad Romadhoni; Yam Saroh; Ani Asryan (JEELS (Journal of English Education and Linguistics Studies), 2022)
EFL teachers are currently considering implementing practical strategies to help students make rapid progress in learning English and reach their learning goals. Simultaneous Roundtable is one of the strategies that are familiar to them. In particular, the Simultaneous Roundtable strategy is examined in this study in order to determine whether it is effective for writing English descriptive essays. Indonesian seventh graders were examined in this experiment. The experimental group applied the Simultaneous Roundtable strategy. The control group then received instruction using a teacher's feedback strategy. The Simultaneous Roundtable strategy was more effective than the traditional teacher feedback strategy for improving the students' descriptive writing skills. Simultaneous Roundtable, therefore, is recommended for EFL teachers to implement since it can be one of the practical teaching strategies that significantly improve students' descriptive writing skills and increase their interpersonal and social skills.